Spatial-temporal variation and modeling of rainwater quality (Research, Society and Development, 2021)
Rainwater harvesting (RWH) is an alternative to the problem of water scarcity. However, its quality must be analyzed before its use, so that it does not represent any danger to the consumer. Thus, the objective of this paper was to analyze the spatial-temporal variation of water quality of rainwater in two cities and observe whether its parameters meet the norm related to the subject. In addition, the concentration of total suspended solids (TSS) that flow into the drainage system was also simulated. Rainwater samples were collected at several points in Congonhas and Ouro Branco - MG, over a period of two years. The results showed that there was spatial-temporal variation in water quality. There were points where the quality met the standard in some moments and did not meet in others, due to its temporal variation. It was also observed that the catchment surface influenced the quality of rainwater, so that the water that came into contact with the roof had its quality deteriorated, at first. However, throughout the rainy event, the quality improved, but at certain times, it was not enough to meet the standard. The rainwater quality simulation, carried out at SWMM, showed high concentrations of TSS, which were higher to that allowed for launching into receiving bodies.